2010
DOI: 10.1017/s0317167100010544
|View full text |Cite
|
Sign up to set email alerts
|

Abrogating HSP Response Augments Cell Death Induced by As2O3 in Glioma Cell Lines

Abstract: 504Malignant gliomas are the most common and lethal tumors of the central nervous system and are resistant to many kinds of treatment, including radiation, chemotherapy, and other adjuvant therapies 1,2 . Although considerable progress has been made in the treatment of glioma, its prognosis is still very poor 3 . The inefficacy of these therapeutic modalities in curing gliomas is due to the resistance of glioma cells and the difficulty of achieving complete tumor resection. There is therefore an urgent need to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 30 publications
2
6
0
Order By: Relevance
“…4244 FKBP·cHSF1 activation afforded a small but significant increase in cellular viability when HEK293T-Rex cells are challenged with heat (Figure 6A) or As(III) (Figure 6B), consistent with the capacity of stress-independent HSF1 activation to protect cells against stress.…”
Section: Resultssupporting
confidence: 52%
“…4244 FKBP·cHSF1 activation afforded a small but significant increase in cellular viability when HEK293T-Rex cells are challenged with heat (Figure 6A) or As(III) (Figure 6B), consistent with the capacity of stress-independent HSF1 activation to protect cells against stress.…”
Section: Resultssupporting
confidence: 52%
“…Differentiation agents for malignant gliomas remain a real challenge. Some studies have shown arsenic trioxide (As 2 O 3 ) and forskolin can also trigger apoptosis and differentiation in glioma cells [39, 40]. In our study, we unexpectedly found a very strong differentiation effect of conditioned MSCs medium.…”
Section: Discussionsupporting
confidence: 55%
“…Human glioma treatment is especially challenging because current treatments, such as chemical therapy, drastically affect patient quality of life. As 2 O 3 has been successfully used for gliomas in a number of clinical trials and experiments because of its significant anticancer property [ 1 , 2 ]. In previous researches, As 2 O 3 (3 to 10 μM) could also induce apoptosis in cultured bone marrow mesenchymal stem cells [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapy and/or radiotherapy are the main approaches for glioma treatment after surgery. As 2 O 3 as an antitumor agent has shown efficacy in treating glioma in laboratory tests [ 1 , 2 ]. Additionally, As 2 O 3 has potential as a mitochondrial toxin that can induce reactive oxygen species (ROS) production; these mainly originate in the intracellular mitochondrial respiratory chain and further toxic byproducts subsequently produced could lead to mitochondrial damage [ 3 ].…”
Section: Introductionmentioning
confidence: 99%